(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The paper Sheds light on one of the most important problems among the whole problems that we find in the history of philosophy, namely, the problem of the relationship between wisdom and Sharia law, trying to disclose the nature of the relationship between wisdom and law in order to detect intellectual conflicts or issues that the philosophers tried to detect the pivotal and key points between wisdom and Sharia law, and philosophy and religion, through the general cultural state prevailing in the Arab society during the Islamic middle ages. In addition, we will try to clarify the theoretical and methodological foundations of the problem of reconciling and highlight the ideological goals that drove the philosophers to reconcile between wisdom and Sharia.